Analgesic Effects Of Annona Muricata Leaf Extract In Paclitaxel And Streptozotocin-Induced Diabetic Neuropathy In Murine Models - Koomson, F.A. (University Of Ghana, 2022)
Background: Annona muricata have demonstrated antinociceptive and anxiolytic effects in animal models through its leaf extracts. This study evaluates the aqueous leaf extract of the plant for possible analgesic properties in hyperalgesia and allodynia associated with paclitaxel-induced neuropathy in mice and streptozotocin (STZ)- induced diabetic neuropathy in rats. Methods:10kg of the coarse crushed leaves was soaked in 3 liters of distilled water to make a decoction, cooled, filtered and freeze dried for use. Sub-acute toxicity test was carried out for 14- days after which blood samples were taken and examined for haematological analysis. Phytochemistry of the extract was conducted and analgesic property was accessed using hot plate test. Irwin test was also conducted to observe alterations in behavior and physiological activity, neurotoxicity and mortality. Diabetic- induced neuropathy in Sprague-Dawley rats was accomplished by injecting 55mg/kg body weight of STZ followed by 120mg/kg body weight of nicotinamide to achieve type 2 diabetes mellitus. Paclitaxel-induced neuropathy was also achieved by injecting ICR mice with 2mg/kg body weight body weight of paclitaxel continuously for 5 days. Parameters which include cold allodynia mechanical hyperalgesia and thermal hyperalgesia were measured before the administration of paclitaxel and on day 1 – 5 and after the administration of paclitaxel. In STZ-induced diabetic neuropathy experiment parameters were measured before the administration of STZ and after the administration of STZ on day 2, 4, 6, 8, 10, 12 and 14. These animals were then treated with Annona muricata extract (AME) (30, 100 and 300 mg/kg body weight), pregabalin (10, 30 and 100 mg/kg body weight) and distilled water as a vehicle daily for 5 days and 14 days continuously in paclitaxel- and diabetic-induced peripheral neuropathy respectively. Pain thresholds were measured on day 1, 2, 3 and 5 in paclitaxel-induced neuropathy experiment and that of STZ-induced - diabetic neuropathic experiment, it was measured from day Results: Annona muricata Extract (AME) showed no toxicity as no death were observed during the 14-day study period in sub-acute toxicity studies. Preliminary phytochemical screening of the extract indicated the presence of secondary metabolites which includes alkaloids, saponins, flavonoids, tannins, glycosides, triterpenoids and sterols. The extract showed analgesic property during the hot plate test. CNS safety pharmacology using Irwin test indicated no mortality when experimental animals were observed for 24 hours after various treatment doses were employed. Observable physiological/ pharmacological effects were noted which include straub tail, defecation, sniffing among others. Relative organ weight of the experimental animals also indicated no obvious abnormally when compared to the control during Irwin’s test. AME and pregabalin produced analgesic properties which was exhibited in paclitaxel and STZ-induced - neuropathy as increased paw withdrawal latencies to mechanical, cold-water stimuli and thermal hyperalgesic tests. Conclusions: The findings from this study suggest that aqueous extract of Annona muricata is sub acutely safe with observable CNS physiological effect and no observable CNS toxicity. Again, the extract possesses an analgesic property as seen in both paclitaxel- and STZ-induced diabetic neuropathy in animal models which may contribute to its traditional use in managing neuropathic pain.
MPhil. Pharmacology
Keywords: Murine Models; Annona Muricata; Streptozotocin-Induced Diabetic; Neuropathy